Asymmetric Synthesis of Dihydrofurans via Organocatalytic Domino Michael–Alkylation Reaction. Issue 6 (24th March 2015) - Feng, Juhua; Lin, Lili; Yu, Kunru; Liu, Xiaohua; Feng, Xiaoming
Abstract The chiral N, N′‐dioxide C‐PrPr2 has been developed as an efficient organocatalyst to catalyze the asymmetric domino Michael–alkylation reaction between cyclohexane‐1, 3‐dione derivatives and bromonitrostyrenes. For dimedone, the corresponding bicyclic 2, 3‐dihydrofurans with two stereocenters were obtained in up to 99 % yield with 95:5 d.r. and 96 % ee. For prochiral 5‐monosubstituted cyclohexane‐1, 3‐diones, the desymmetrization reaction provided the bicyclic 2, 3‐dihydrofurans with three stereocenters in up to 90 % yield with 82:18 d.r. and 94 % ee. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>